A candidate single nucleotide polymorphism in the 3' untranslated region (rs17878624) of survivin gene for NSCLC - Aynaci, Engin; Coskunpinar, Ender; Yildiz, Pinar (Cellular and Molecular Biology, 2018)
Survivin is a gene that locates on human chromosome 17q25 and contains 142 amino acid. Survivin (BIRC5) is the first one of the found inhibitors of apoptosis proteins (IAPs) that is an important protein family and regulates apoptosis. It is expressed particularly in cancer cells. 3'UTR region of gene has components that is necessary for gene function and this region plays a critical role in the regulation of posttranscriptional regulation of the gene expression. Therefore, polymorphisms in this region may affect the function of the gene. The purpose of the study is to investigate possible relationship, that is associated with development and prognosis of the disease, between the 3 'UTR region (rs17878624) polymorphism and NSCLC in a Turkish society.